THE CONCEPT OF LONE-WOLF TERRORISTS (Annual of the Faculty of Philosophy in Skopje, 2019)
The nature of terrorism has changed significantly over the last decade. In recentyears, the phenomenon of so-called lone wolf terrorism has increased with moreand more attacks perpetrated by single actors. The shifting nature of terrorism hasprompted a debate over how to accurately describe individuals that act independentlyof a terrorist organization’s chain of command. The lone wolf concept needs to bere-evaluated and adapted to changed circumstances. The purpose of this paper willbe focused on one of the most unpredictable forms of terrorism acts - those committedby a single individual, a so-called ”lone wolf terrorist”. Politically, the conceptlone wolf is used to reassure the public and communicate that the danger is no longerimmanent. Academically as well as practically, the concept entails more thanthis reassurance. The most difficult part in detecting a lone wolf is that their attacksoccur in the context of multiple ideological frameworks and are not confined to a singlegroup or system of belief. Currently, there are more questions than answers onthe content and validity of the lone wolf concept, but we should be alert and awarethat the external conditions have changed, and old responses may not be appropriateanymore to present-day lone actor terrorism.
Keywords: LONE-WOLF TERRORISTS; EXTREMISM; ATTACKS; THREAT; RADICALIZATION